2015
DOI: 10.1016/j.antiviral.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the global virome: Identification and characterization of HCV-related animal hepaciviruses

Abstract: Recent advances in sequencing technologies have greatly enhanced our abilities to identify novel microbial sequences. Thus, our understanding of the global virome and the virome of specific host species in particular is rapidly expanding. Identification of animal viruses is important for understanding animal disease, the origin and evolution of human viruses, as well as zoonotic reservoirs for emerging infections. Although the human hepacivirus, hepatitis C virus (HCV), was identified 25 years ago, its origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
86
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 76 publications
2
86
2
2
Order By: Relevance
“…Furthermore, the detection of viral RNA at comparable loads in the French sera sampled in 1979 and Bulgarian sera sampled in 2015 implicated suitability of the non-recently sampled specimens for viral RNA detection. Viral clearance is typically delayed in HV infection, including infection with EqHV in horses (7). In our study, three serial individual specimens taken at different time points over 2 weeks (May-June 1979) were available from the RNA-positive donkey sampled in France.…”
Section: Molecular Detection Of Eqhv In Donkeysmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the detection of viral RNA at comparable loads in the French sera sampled in 1979 and Bulgarian sera sampled in 2015 implicated suitability of the non-recently sampled specimens for viral RNA detection. Viral clearance is typically delayed in HV infection, including infection with EqHV in horses (7). In our study, three serial individual specimens taken at different time points over 2 weeks (May-June 1979) were available from the RNA-positive donkey sampled in France.…”
Section: Molecular Detection Of Eqhv In Donkeysmentioning
confidence: 99%
“…The evolutionary origins of HCV have remained obscure (6). Recent studies identified numerous hepaciviruses (HVs) in bats, rodents, monkeys, and peridomestic animals (7,8). Considering the absence of HCV-related viruses in higher primates (9), as well as the existence of genetically diversified nonprimate HVs, mammals other than primates may have shaped primordial HCV evolution (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Searches for related viruses in primates were unsuccessful, leaving the history and origin of HCV unknown. Recently, developments in deep sequencing methods accelerated identification of a number of related viruses (1). Nonprimate hepacivirus (NPHV) was the first to be discovered, initially identified in samples from dogs and termed canine hepacivirus (2).…”
mentioning
confidence: 99%
“…Recently, multiple new hepaciviruses have been identified in dogs (1), horses (2), bats (3,4), rodents (3,5), nonhuman primates (6), rats (7), and cattle (8,9). Among them, nonprimate hepacivirus (NPHV), initially described to infect dogs and subsequently horses, is the closest homolog of HCV and thus represents a unique model to study differences in hepacivirus pathogenesis of HCV and HCV-related viruses (10,11).…”
mentioning
confidence: 99%